Feeding spice crops for quality produce - Anandaraj, M; Dinesh, R; Srinivasan, V; Hamza, S; Bini, Y K (Indian Horticulture, 2019)
Soi l micronutrient deficiencies drastically reduce the yield of spices. Hence, crop specific micronutrient formulations have been developed and commercialized for ginger, turmeric, black pepper and cardamom. Yield increase of 20-25% have been realized at farmers’ fields. Plant growth promoting rhizobacteria (PGPR) have been extensively employed in agriculture for enhanced yield and disease suppression. The PGPR formulations have been developed for ginger, black pepper and seed spices. These PGPR formulations enhance growth besides being effective replacements for chemical fertilizers/fungicides. The delivery of PGPR through encapsulation has been a major breakthrough in biofertilizer industry. What makes this technology more exciting is that this encapsulation process can be used to deliver all kinds of agriculturally important microorganisms.